Pengaruh Tingkat Kekerasan Buah dan Letak Benih dalam Buah terhadap Viabilitas dan Vigor Benih Kakao (Theobroma cacao L.) - Nanda Fadila; Syamsuddin Syamsuddin; Rita Hayati (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2016)
Effect of the Pod Hardness Level and Seed Position in Pod on Cocoa Seed (Theobroma cacao L.) Viability and Vigor ABSTRACT. The study was aimed to recognize the effect of the pod hardness level, seed position in pod, and the interaction between them on cocoa seed viability and vigor. The design used was a factorial completely randomized design (CRD) with 3 replicates. The level of pod hardness as the first factor consisted of 4 levels: 3.5 kg/second, 3.0 K ≤ 3.5 kg/second, 2.5 K ≤ 3.0 kg/second and 2.0 K ≤ 2.5 kg/second. The position of seed in pod as the second factor covers 3 levels, they are both ends and the middle of the pod. Observation conducted to the seed dried weight (BK), maximum growth potency (PTM), germination capacity (DB), vigor index (IV), growth speed (KCT), simultaneity growing (KST), time needed to reach 50% from the total of relative germination (T50) and dry weight of normal sprouts (BKKN). The results showed that the highest viability and vigor of cocoa seed was found from 2.5 K ≤ 3.0 kg/second of pod hardness level. The highest viability and vigor of cocoa seed came from the middle of the pod. The best combination was found from 2.5 K ≤ 3.0 kg/second of pod hardness level in the middle of the pod.